BENCHMARKING HEAD OF MADRASAH IN JAMBI PROVINCE - Emmi Kholilah Harahap (International Journal of Southeast Asia, 2020)
The purpose of this research is to know the success of benchmarking of madrasah head in transforming madrasah, to know benchmarking of head of madrasah, to know transformation that happened at madrasah, and to know benchmarking of madrasah head to transform madrasah. The research methodology used is descriptive qualitative approach. Data collection techniques using observation, interviews and documentation. Analysis of the data using the model of Miles and Huberman and data validity technique uses triangulation data. The results show that the success of madrasah head benchmarking in transforming with active commitment in managing madrasah, understanding the advantages and weaknesses of madrasah, innovating in madrasah, and applying benchmarking results in madrasah. Benchmarking process is self-evaluation of madrasah program, comparison with referral madrasah, reflection of madrasah performance and backbiting towards benchmarking of madrasah. The madrasah transformation covers the aspects of input, process transformation in madrasah, transformation of madrasah output and transformation of madrasah culture. The conclusion of this research can be seen that through benchmarking the head of madrasah can make the head of madrasah do madrasah transformation. The implication of this research is that benchmarking done by head of madrasah is not necessarily self-done. This requires the responsibility and commitment of all madrasahs in it, managerial skills, adequate human resources, and empowerment of all personnel in the madrasah.